Variability of Sea Breezes Over the Cameroonian Coast and Their Interaction With the West African Monsoon - Kouogang Tchuenkam, Fabius Cédric; Mama, Anselme Crépin; Gah-Muti, Salvanus Yevalla; Araujo, Moacyr (Frontiers in Earth Science, 2022)
Characteristics of sea breeze over two coastal areas of Cameroon were studied. The study used 3-hourly wind (speed and direction), rainfall and atmospheric pressure data for 4 years (2006-2009) at Tiko and 5 years (2011-2015) at Ebodje to examine various characteristics of sea breeze. Statistics are presented that describe the occurrence, onset and cessation, and strength of the sea breezes. The frequency of occurrence clearly shows two regimes by two maxima (November and March) at Tiko and (January and July) at Ebodje. The results show that sea breeze usually starts as a light onshore surface wind few hours after the sunrise and has a mean duration of about 9h at Tiko. It is found that the sea breeze occurs during all seasons in this region. Sea breeze occurrence is found to be strongly influenced by the West African monsoon. Sea breezes onset and cessation times show a pronounced seasonal variation. Sea breeze strength is greater at Tiko than at Ebodje during the West African monsoon season. Average daily hodographs for Tiko reveals the sea breeze circulation is both clockwise and anticlockwise rotation. There would be a significant seasonal effect of large-scale flows on sea breeze hodograph patterns. A windroses analysis at Ebodje shows a high temporal variability of sea breeze frequencies at 09:00 (Local Standard Time: LST) in the south direction (36%), after at 15:00 LST in west direction (26%), because of the preponderance of calm atmospheric situations conducive to its onset. Therefore, the circulation of the sea breeze is influenced by local factors (topography, vegetation). This phenomenon in the coastal regions of Cameroon can be the main factor controlling the transport of accidental near shore oil slicks and air pollutants.